Virtual classroom management solutions for COVID–19 related anxiety issues - Bilal Qureshi; Peter Frost; Benjamin Spink (Journal of English Language Teaching Innovations and Materials (Jeltim), 2022)
The COVID-19 pandemic has brought immeasurable changes in almost every aspect of our lives and education is no exception. Following social distancing policies, the vast majority of educational institutions across the globe have shifted their academic structure from traditional face-to-face classes to online classes through a video conferencing software ‘Zoom’ as a synchronous method of instructions. Besides the fact that a complete diversion of classes toward online education has brought hope to many students to continue their education amid this time of the pandemic, there are many drawbacks to online learning, including online learning anxiety, that keep many students from achieving their learning goals. This study is designed to investigate Korean university students’ attitude toward online learning in general and their feelings of anxiety (if any) in particular when using video conferencing software ‘Zoom’. This mixed method study was conducted in two universities in Korea. Participants (n=132) were both male (n=61, 46.2%) and female (n=71, 53.8%) undergraduate students enrolled in the English linguistics department. The hypothesis stated that students with different socio-economic backgrounds have different attitudes towards online learning, which affects their feelings of anxiety for online learning. Quantitative data was collected in the form of survey questions, and interviews were conducted with randomly selected students (n=13) to obtain qualitative data. The findings suggest a few pedagogical implications for both teachers and students that include interventions and support by the experts to feel less isolated in online classes, and provision of a more user-friendly platform to be connected with teachers and peers.